IMPLEMENTASI METODE AHP DALAM MENENTUKAN KARYAWAN TERBAIK PT. SAKURA ANUGRAH PRATAMA - Dede Supiyan; Eko Apriyanto (Journal of Research and Publication Innovation, 2026)
Employee performance appraisal is a crucial aspect in human resource management, especially in an effort to identify outstanding individuals who contribute significantly to the achievement of organizational goals. However, there are still many companies that face obstacles in the assessment process that are not objective, lack clear indicators, and are done manually, causing injustice and reducing employee motivation and loyalty. This study aims to design and implement a decision support system based on Analytical Hierarchy Process (AHP) methods in determining the best employees at PT. Sakura Is The Main Character. The AHP method was chosen because of its ability to process multicriteria problems quantitatively and systematically through paired comparisons to determine the weight of each criterion. The system developed is implemented in the form of a web-based application to facilitate the evaluation process digitally and structured. The results showed that this system is able to provide an objective, transparent, and accurate assessment based on predetermined criteria, namely performance, discipline, skills, and responsibility. Thus, this system is expected to improve the quality of decision-making and create a fairer work environment and motivate employees to continue to improve their performance.